VD_FINDINFO AI 327/10 - 361/2012 vom 2. November 2012 - VD Tribunal cantonal (2012)
RENTE D'INVALIDITÉ, FORCE PROBANTE, MESURE DE RÉADAPTATIONASSURANCE SOCIALE | 28 al. 2 LAI, 4 al. 1 LAI, 8 al. 1 LPGA